2014
DOI: 10.12688/f1000research.4645.2
|View full text |Cite
|
Sign up to set email alerts
|

False memory susceptibility is correlated with categorisation ability in humans

Abstract: Our memory is often surprisingly inaccurate, with errors ranging from misremembering minor details of events to generating illusory memories of entire episodes. The pervasiveness of such false memories generates a puzzle: in the face of selection pressure for accuracy of memory, how could such systematic failures have persisted over evolutionary time? It is possible that memory errors are an inevitable by-product of our adaptive memories and that semantic false memories are specifically connected to our abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…This suggestion establishes a point of contact between the DRM illusion and theories of category/context learning. In support of such process, the DRM illusion is correlated with the ability to identify words that share a common category (Hunt & Chittka, 2014); and manipulations like those used in the present study influence context learning in animals. For example, just as early list manipulations in the DRM protocol appear to reduce false lure memories by interfering with formation of the list category or context, exposure to an aversive event immediately upon placement in a distinctive chamber interferes with formation of a context representation in animal studies (Bae et al, 2015;Fanselow, 1986;Kiernan & Westbrook, 1993;Landeira-Fernandez et al, 2006;Lingawi et al, 2018, for evidence that a distractor can disrupt the semantic priming effect, see Dannenbring & Briand, 1982;Davelaar & Coltheart, 1975;Foss, 1982;Joordens & Besner, 1992;Masson, 1991;McNamara, 1992;Ratcliff & McKoon, 1988).…”
Section: Discussionsupporting
confidence: 56%
“…This suggestion establishes a point of contact between the DRM illusion and theories of category/context learning. In support of such process, the DRM illusion is correlated with the ability to identify words that share a common category (Hunt & Chittka, 2014); and manipulations like those used in the present study influence context learning in animals. For example, just as early list manipulations in the DRM protocol appear to reduce false lure memories by interfering with formation of the list category or context, exposure to an aversive event immediately upon placement in a distinctive chamber interferes with formation of a context representation in animal studies (Bae et al, 2015;Fanselow, 1986;Kiernan & Westbrook, 1993;Landeira-Fernandez et al, 2006;Lingawi et al, 2018, for evidence that a distractor can disrupt the semantic priming effect, see Dannenbring & Briand, 1982;Davelaar & Coltheart, 1975;Foss, 1982;Joordens & Besner, 1992;Masson, 1991;McNamara, 1992;Ratcliff & McKoon, 1988).…”
Section: Discussionsupporting
confidence: 56%
“…However, individual differences based on thought and reasoning have been little studied: for example, it has been observed that false memories are associated with convergent thinking ( Dewhurst et al, 2011 ), categorization ability ( Hunt and Chittka, 2014 ) and negatively correlated with fluid and crystallized measures of intelligence ( Zhu et al, 2010 ). A more prolific line of research has investigated the relationship between Need for Cognition (NFC) ( Graham, 2007 ; Leding, 2011 , 2013 ; Wootan and Leding, 2015 ; Parker and Dagnall, 2018 ) and false memories.…”
Section: Introductionmentioning
confidence: 99%